Metaxenia effects on fruit quality attributes in diverse passion fruit (Passiflora edulis) crosses - Utama, Syahrul; Hayati, P. K. Dewi; Hamid, Hasmiandy; Syarif, Auzar; Ira Desri Rahmi (Agriculture and Natural Resources, 2026)
Importance of the work: Metaxenia as a result of cross-pollination in passion fruit affects the quality of the fruit produced. Objectives: To investigate the effect of metaxenia on fruit quality produced from crosses of different types of passion fruit. Materials and Methods: A completely randomized design was used, with crossing parental and crosses between passion fruit types as treatments, namely red-skinned with an oval-shape (ML), red-skinned with a round-shape (MB), yellow-skinned with yellow-pulp (KK), yellow-skinned with orange-pulp (KO) from Passiflora edulis f. edulis and yellow-skinned from Passiflora. edulis f. flavicarpa (FF). Results: Crossing various types of passion fruit produced metaxenia effects on the characteristics of fruit length, fruit shape, fruit pulp color, total soluble solid value and sweetness of passion fruit. However, the characteristics of fruit width, fruit weight, number of seeds, total titratable acid and edible portion percentage were not influenced by the source of pollen used in the cross. The cross combination between the KO and ML passion fruit types produced superior fruit from both parents in terms of fruit length (up to 8.62 cm), total soluble solids (reaching 17.2°Brix) and fruit sweetness (score of up to 3.40). However, the metaxenia effect from the other cross combinations tended to reduce fruit quality. Main finding: The effect of metaxenia on passion fruit tended to reduce fruit quality. Therefore, it is advisable to avoid the co-cultivation of multiple passion fruit types within the same growing area, to maintain superior fruit quality, especially in fruit sweetness.